2019
DOI: 10.3906/elk-1806-124
|View full text |Cite
|
Sign up to set email alerts
|

An ambient assisted living system for dementia patients

Abstract: Dementia is a major health and social care challenge of today and the near future as a result of increased human lifespan. Currently, there is no therapeutic solution for dementia, but a solution for managing the wandering behavior of dementia patients can be provided by an ambient assisted living system. In this paper, the design and implementation of iCarus, which is an intelligent ambient assisted living system for dealing with wandering behavior in early stages of dementia, is described. The aim of iCarus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, in this review, many studies reported on the utilization of ad-hoc instruments. Examples of poor practices from a methodological quality point of view are the use of questionnaires developed purposively for a study without any attempt to assess its validity by an expert panel or against a gold standard and without specifying the questions and the process of development (e.g., [35,36,38,39,41,49,55,63,73]), extracting some questions from previously validated instruments compromising their validity and reliability (e.g., [53]), or assessing reliability but not validity (e.g., [52,60]). Ensuring validity is ensuring that an instrument is assessing what is supposed to be assessed and ensuring reliability is ensuring that the instruments give consistent results across repeated assessments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in this review, many studies reported on the utilization of ad-hoc instruments. Examples of poor practices from a methodological quality point of view are the use of questionnaires developed purposively for a study without any attempt to assess its validity by an expert panel or against a gold standard and without specifying the questions and the process of development (e.g., [35,36,38,39,41,49,55,63,73]), extracting some questions from previously validated instruments compromising their validity and reliability (e.g., [53]), or assessing reliability but not validity (e.g., [52,60]). Ensuring validity is ensuring that an instrument is assessing what is supposed to be assessed and ensuring reliability is ensuring that the instruments give consistent results across repeated assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring validity is ensuring that an instrument is assessing what is supposed to be assessed and ensuring reliability is ensuring that the instruments give consistent results across repeated assessments. Although there might be reasons to develop or adapt a scale/questionnaire, its validity and reliability must be evidenced [77], which was not the case of the questionnaires used in 37% of the studies included in this review (i.e., [35,36,38,39,41,49,52,53,55,60,63,73]). The finding that SUS was the most commonly usability scale reported in the included studies (i.e., [43,45,54,56,58,59,61,[64][65][66][67][68][69][70][71]74]) is in line with a previous review on user-centered usability evaluation [78] and it suggests that this is a widely accepted instrument, usually regarded as a golden standard in terms of usability evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations